Pengoptimuman algoritma pengesanan batu loncatan dalam sistem pengesanan pencerobohan - Omar, Mohd. Nizam (2005)
Detection of a network intrusion and manual response without any further action does create a problem known as time gap. Time gap is duration between detection and response. Previous researches have used some approaches like intelligent agent and IDS adoption to solve time gap problem. However, they do not consider the aspect of intrusion response mechanism. The purpose of this study is to optimize the stepping stone algorithm, which is part of intrusion response mechanism. In this research, special Top-Down methodology has been used to optimize the stepping stone algorithm. It is achieved by analyzing five stepping stone algorithms, in which each algorithm is divided into three main parts. The parts are packet capture, identification and comparison. Among these algorithms, the best approach which produces minimum processing time from each main part has been deployed and tested as a complete stepping stone algorithm. The results from both the optimized approach and existing algorithm are compared. From this comparison, the optimized algorithm gives the best result. The finding of this research suggests that time gap can be reduced through the optimization of the stepping stone algorithm.